Male Portraits by Assamese Women Writers. Issue 1 (June 2017) - Raimedhi, Indrani
This article reflects how women writers in Assam create their male characters from the standpoint of their own vulnerable and precarious existence in a patriarchal society. The author has interviewed prominent Assamese women writers Mamoni Raisom Goswami, Anuradha Sharma Pujari, Rita Chowdhury, Arupa Patangia Kalita, Manorama Das Medhi, Leena Sarma, Moushumi Kandali and Karabi Deka Hazarika over the years to write this piece.